2014
DOI: 10.1590/1677-3225v13n2a07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of push-out bond strength of a MTA-based root canal sealer

Abstract: . Methods: Thirty extracted single-root human teeth of similar sizes and circular canals were prepared using #3 and #2 Gates Glidden drills in the cervical portion of the canal and K3 ® rotary instruments to a size #25/0.06 to working length. Irrigation with 0.5 mL 2% chlorhexidine gel was used before and 1 mL saline after each instrument. The smear layer was removed with 3 mL 17% EDTA for 3 min. The samples were sectioned horizontally into eight 1±0.1 mm-thick serial slices and then the push-out test was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
2
33
0
3
Order By: Relevance
“…Gurgel-Filho et al 6 showed that the lowest bond strength to root dentin was MTA-Fillapex which is similar to the present study where Fillapex sealer has the lowest mean marginal and apical adaptation at coronal as well as in the apical third among the three sealers used in the study. When the sealers come into contact with phosphate-containing fluids, the set material releases calcium and hydroxyl ions and forms apatite; this theory was put forth by Sarkar et al 10 Reyes-Carmona et al, 11 in their study done in 2009, observed that the formation of an interface layer by apatite with tag-like structures plays a crucial role, this apatite is formed by MTA and phosphate-buffered saline which gets deposited within collagen fibrils, and it promotes controlled mineral nucleation on dentin formed.…”
Section: 9supporting
confidence: 90%
See 1 more Smart Citation
“…Gurgel-Filho et al 6 showed that the lowest bond strength to root dentin was MTA-Fillapex which is similar to the present study where Fillapex sealer has the lowest mean marginal and apical adaptation at coronal as well as in the apical third among the three sealers used in the study. When the sealers come into contact with phosphate-containing fluids, the set material releases calcium and hydroxyl ions and forms apatite; this theory was put forth by Sarkar et al 10 Reyes-Carmona et al, 11 in their study done in 2009, observed that the formation of an interface layer by apatite with tag-like structures plays a crucial role, this apatite is formed by MTA and phosphate-buffered saline which gets deposited within collagen fibrils, and it promotes controlled mineral nucleation on dentin formed.…”
Section: 9supporting
confidence: 90%
“…The final obturation neither retracts nor resorbs. 6 This in vitro study compares marginal adaptation and sealing ability (MTA-Fillapex, AH Plus, Endofill sealers) of root canal sealers.…”
Section: Jcdpmentioning
confidence: 99%
“…That also can be applied to EndoSequence BC which also forms a hydroxyapatite hybrid layer upon setting (23,24,25). This result came in accordance with the results of other studies (8,15,23,25) and contradict to others. Assmann et al (20) reported no significant difference between the bond strength of AH Plus and the MTA Fillapex sealers, while Naser and Al-Zaka (24) and Shokouhinejad et al (26) reported no significant difference between AH Plus and BC sealers.…”
supporting
confidence: 85%
“…It has been suggested that push-out test provides a good evaluation of bond strength because the load applied parallel to the dentine bonding interface simulates clinical stresses (10,14,15,16). It has the advantages of testing different sections in the root canal besides the simplicity of sample preparation in comparison to other tests (17).…”
mentioning
confidence: 99%
“…Because of the poor adhesiveness of gutta-percha, root canal sealers must be used to fill imperfections and increase adaptation of the root filling material to the canal walls to avoid any chance for leakage and failure [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%